Preserving Education as a Public Good: Lessons from the Grassroots. Issue 3 (May 2020) - Ferman, Barbara
The article provides an overview of my book, The Fight for America's Schools: Grassroots Activism in Education . The book examines how grassroots activists in Pennsylvania and New Jersey challenged various neoliberal reforms in education such as high stakes testing, school closures, state takeovers of local school districts, and charter school expansion. The four case studies focus on who the activists were, how they became involved, the challenges they faced, and the prospects for coalition building across different constituent groups. The comparative analysis reveals the role of political, organizational, demographic, and historical factors in shaping how activism played out in each location and in its effectiveness.